RIBOSOMAL COMPLEX IN PROPHYLAXIS AND TREATMENT OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN - A.A. Alekseeva; L.S. Namazova-Baranova; R.M. Torshkhoeva; E.A. Vishneva; Yu.G. Levina ("Paediatrician" Publishers LLC, 2010)
Acute respiratory infections (ARI) are widespread in children regardless of age and region of living; they are characterized with big amount of infectious agents and absence of a trend to morbidity decrease. Drugs for nonspecific prophylaxis (immunostimulators and immunomodulatory agents) are frequently used for prevention of ARI. There are plenty of immunomodulating agents; the wellstudied medication with systemic action with good efficacy and safety in pediatric practice is ribosomal-proteoglycan complex. The article presents the description of clinical experience of treatment with this complex in pediatric practice.Key words: children, acute respiratory infections, prophylaxis, treatment, ribosomal complex.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):127-130)